The Interplay Between Replication Capacity of HIV-1 and Surrogate Markers of Disease. (21st April 2022) - Rindler, Audrey E; Kusejko, Katharina; Kuster, Herbert; Neumann, Kathrin; Leemann, Christine; Zeeb, Marius; Chaudron, Sandra E; Braun, Dominique L; Kouyos, Roger D; Metzner, Karin J; Günthard, Huldrych F
Abstract: Background: HIV-1 replication capacity (RC) of transmitted/founder viruses may influence the further course of HIV-1 infection. Methods: RCs of 355 whole-genome primary HIV-1 isolates derived from samples acquired during acute and recent primary HIV-1 infection (PHI) were determined using a novel high-throughput infection assay in primary cells. The RCs were used to elucidate potential factors that could be associated with RC during PHI. Results: Increased RC was found to be associated with increased set point viral load (VL), and significant differences in RCs among 13 different HIV-1 subtypes were discerned. Notably, we observed an increase in RCs for primary HIV-1 isolates of HIV-1 subtype B over a 17-year period. Associations were not observed between RC and CD4 count at sample date of RC measurement, CD4 recovery after initiation of antiretroviral treatment, CD4 decline in untreated individuals, and acute retroviral syndrome severity scores. Conclusions: These findings highlight that RCs of primary HIV-1 isolates acquired during the acute and recent phase of infection are more associated with viral factors, that is set point VL, than with host factors. Furthermore, we observed a temporal increase in RC for HIV-1 subtype B viruses over a period of 17 years. Clinical Trials Registration: NCT00537966. Abstract : Using 355 primary HIV-1 isolates of acute and recently HIV-1–infected patients, we elucidated that replication capacity is associated with set point viral load, HIV-1 subtype, and viral diversity, as well as calendar year.